Good corporate governance as moderator of the diversification of portfolios - Isnalita, Adilla Artantino, (Opción, 2020)
The purpose of this study was to empirically examine the effect of credit portfolio diversification on credit risk with Good Corporate Governance (GCG) as a moderating variable. The samples in this study were 38 commercial banks listed on the Indonesia Stock Exchange from 2013 to 2015. The data in this study were analyzed using moderated regression analysis with the SPSS software. The results of the study proved that working capital loans had a negative and significant effect on credit risk. In conclusion, GCG can moderate the influence of the diversification of the loan portfolio on the level of credit risk.